Application of the method of averaging to boundary value problems for differential equations with non-fixed moments of impulse - Stanzhytskyi, O.M.; Uteshova, R.E.; Mukash, M.; Mogylova, V.V. (Carpathian Mathematical Publications, 2022)
The method of averaging is applied to study the existence of solutions of boundary value problems for systems of differential equations with non-fixed moments of impulse action. It is shown that if an averaged boundary value problem has a solution, then the original problem is solvable as well. Here the averaged problem for the impulsive system is a simpler problem of ordinary differential equations.